تحليل الأخطاء الإملائية والخطية في الكتابة العربية لطلبة المدرسة الثانوية باب السلام تامبار جوكوراطا جومبانج: Analisis Kesalahan Imlak dan Khat pada Tulisan Arab Siswa Madrasah Tsanawiyah Babussalam Tambar Jogoroto Jombang - Akbar, Dhoyfun (STAI At-Tahdzib Rejoagung Ngoro Jombang, 2024)
The difference between Arabic and pattern writing have a big effect in the students at Babussalam Tambar Jombang, and speciallyin Arabic writing. The goal of writing studies in this high school is to make the student able to write correctly, and without mistakes. But, the students do not have enough capacities and potential to realize this goal which create an obstacle and problem for them. The researcher uses in this thesis, the descriptive analyses qualitative method. It is renamed by